Rebalancing Tools for Comprehensive Real Estate Management: Modeling the Demand Function for Mortgage Buyers - Tsvetkova Liudmila; Orlaniuk-Malitskaia Larisa; Khuzhamov Leonid; Ermolaeva Alexandra (Studies in Business and Economics, 2024)
The problem of real estate management in the growing environment of electronic and smart investment and sales tools is becoming increasingly important in matters of rebalancing the value of property and calculating the risks arising from implementing the mortgage loan agreement. This study’s purpose is to investigate the prospect of using a model for planning insurance portfolios with an account of the needs of consumers to insure the contract’s lifecycle in the face of rising uncertainty. The basis for the investigation was Kahneman and Tversky’s perspective theory. It allowed the unveiling of the difference between the need to fulfil obligations and the need to preserve wealth. The paper modelled and tested the utility hypothesis of homeownership as well as constructed a value function model for the analysis of insurance needs. To model the function’s expression and approximate the dynamics of the premium functions, the Approximation of One Variable Function tool was used. The assumption on the maximum growth in insurance premiums on equipment and furnishings for homes purchased with mortgages at 30-35% of the contract period was confirmed. It was proved that the utility of outstanding debt increases as the debt is paid.